Academic skills for improving success: A proposal oriented to students in post-graduation cycles - Mauritti, R.; Belchior-Rocha, H.; Pintassilgo, S.; Monteiro, J. (EDULEARN23 Proceedings, 2023)
The increase in the number of students entering advanced studies, master's and doctoral degrees, has been associated with a diversification of student profiles, which present different levels of academic preparation and a diversity of educational and professional paths, not always aligned with the requirements requested of them. Aware that the present challenges also involve the institutionalization of training in transversal academic skills designed for postgraduate cycles, we share in this paper some pedagogical tools, meanwhile designed and operationalized in a Public University in Portugal, which aim to position student profiles that are initially very asymmetric, on a common level of technical and scientific ability to build critical thinking and prepare arguments, both written and oral, through a transversal training offer. In a diagnostic phase were identified factors such as: some students' lack of direct field research experience (or very little of it) and, in Portugal, many enter post-graduate training without ever having had any work experience, while others seek post-graduate training after years outside academia, all of which leads to a diversity of profiles, to which we can also add a significant portion of those who come from different parts of the world and who seek to associate the educational project with intercultural experience. All this diversity gives a dynamic to the classrooms that, often, while challenging, is also very enriching. First of all, it challenges teachers about the strategies and pedagogical practices that best meet the general challenges that guide us in our teaching service: arousing curiosity, promoting new learning, guiding students in collaborative work that facilitates the objectives they want to achieve, and instructing them so that they can autonomously carry out in-depth, theoretically and empirically informed research. However, regardless of the good intentions and sense of responsibility of the parties involved, this task, involving the teacher-student relationship is often not made easy, mainly because the set of students/class is not only increasingly diverse among themselves, but is also increasing in number of students with these specific needs.